Outcome of non-surgical treatment of proximal femur fractures in the fragile elderly population. Issue 7 (July 2019) - Frenkel Rutenberg, Tal; Assaly, Aseel; Vitenberg, Maria; Shemesh, Shai; Burg, Alon; Haviv, Barak; Velkes, Steven
Highlights: There are currently no criteria to indicate which patients with fragility hip fracture should not undergo surgery. Patients who were not operated were compared to the most fragile patients (higher ACCI score) who were surgically treated Surgical treatment was correlated with increased 1-year survival even in patients with a higher burden of co-morbidities. Short term survival, in-hospital complications and 1-year readmissions were unaffected by treatment choice. Abstract: Introduction: With the aging of the population the rate of fragility hip fractures increases. While medical recommendations are for hasten surgical treatment, for some older patients burdened with severe comorbidities, this might be risky. Aims: To compare the outcomes of patients treated non-surgically to those of the most fragile patients treated surgically. Patients and methods: A retrospective cohort study, of individuals aged ≥65 years who presented with fragility hip fractures between 01.01.2011-30.06.2016, to a primary trauma center. Patients treated surgically were stratified according to their age-adjusted Charlsons' comorbidity index (ACCI) score. Patients in the upper third of ACCI score, representing the more fragile population, were compared to patients treated non-surgically. Results: 847 patients presented with fragility fractures. 94 (11%) were treated non-surgically and 753 (89%) underwent surgery. Medical reasons were the leading cause for non-surgical treatment (61.7%). Surgically-treated patients were stratified according to their ACCI and 114 patients with ACCI > 9 were chosen for comparison. While both groups were comparable in terms of age, the non-surgical treatment group had more female patients (p. = 0.026) and a smaller proportion of independent walkers (p < 0.001). The ACCI was higher for the surgical treatment group (p < 0.001). In-hospital mortality was similar (14.9% and 18.1% for the operative and non-surgical groups respectively, P. = 0.575). However, one-year mortality was significantly higher for the non-surgical group (48.2% vs. 67.0%, P. = 0.005). The rates of in-hospital complications and 1-year readmissions were similar. Conclusions: Operative treatment for fragility hip fracture reduces long-term mortality rates even in the more fragile patients, compared to non-surgical treatment.